Tactile feedback system of high-frequency vibration signals for supporting delicate teleoperation of construction robots. (2nd June 2020) - Nagano, Hikaru; Takenouchi, Hideto; Cao, Nan; Konyo, Masashi; Tadokoro, Satoshi
ABSTRACT: This study proposes a methodology to deliver contact information on construction robots to the remote operator by transmitting measured collision vibrations, which are often beyond the human-perceivable range. We focus on the human capacity to discriminate the envelope of high-frequency vibrations as an essential cue to perceive contact materials and collision conditions. The proposed method preserves the envelope shapes with amplitude-modulated waves with a single carrier frequency in the human sensitive range. In the preliminary experiments, a miniature shovel digging experiment confirmed that the proposed method improves the discriminability of the contact materials and sliding velocities. A psychophysical experiment also showed that the participants could discriminate the envelope differences irrespective of the carrier frequency. The proposed method was applied to the tactile transmission system for a construction robot developed in the ImPACT program. A vibration sensor was attached on the robot arm, and the vibrotactile feedback was applied to the operator's wrist. Performance evaluations under a delicate teleoperated task (insertion of a bar into bricks) showed that the peak force was reduced by the proposed method significantly for two out of the three participants. The results show that our proposal could improve the maneuverability of teleoperation. GRAPHICAL ABSTRACT: UF0001